2016
DOI: 10.1088/0957-4484/27/6/064001
|View full text |Cite
|
Sign up to set email alerts
|

A synergistic approach to the design, fabrication and evaluation of 3D printed micro and nano featured scaffolds for vascularized bone tissue repair

Abstract: 3D bioprinting has begun to show great promise in advancing the development of functional tissue/organ replacements. However, to realize the true potential of 3D bioprinted tissues for clinical use requires the fabrication of an interconnected and effective vascular network. Solving this challenge is critical, as human tissue relies on an adequate network of blood vessels to transport oxygen, nutrients, other chemicals, biological factors and waste, in and out of the tissue. Here, we have successfully designed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
90
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 136 publications
(90 citation statements)
references
References 76 publications
0
90
0
Order By: Relevance
“…Our findings were in agreement with a recent study showing that HUVECs cultured on pure PLA scaffolds exhibited larger and more highly developed vascular structures compared to those on the nano-HAP-conjugated scaffolds. 15 These observations collectively indicated a negative effect of HANPs on the function of ECs. The biological responses of HANPs may be the results of either their direct impacts on ECs or via the modulation of other factors, such as VEGF, which is a wellknown angiogenic factor.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Our findings were in agreement with a recent study showing that HUVECs cultured on pure PLA scaffolds exhibited larger and more highly developed vascular structures compared to those on the nano-HAP-conjugated scaffolds. 15 These observations collectively indicated a negative effect of HANPs on the function of ECs. The biological responses of HANPs may be the results of either their direct impacts on ECs or via the modulation of other factors, such as VEGF, which is a wellknown angiogenic factor.…”
Section: Discussionmentioning
confidence: 89%
“…It has been reported that ECs maintain biochemical and morphological markers of healthy endothelium in the presence of HAP nanocrystals. 14 Holmes et al 15 conjugated polylactic acid (PLA) scaffolds with nano-HAP. Their experiments showed that ECs could grow on the surface of the scaffolds, and nano-HAP improved cell adhesion.…”
mentioning
confidence: 99%
“…3D printing is evolving into an unparalleled biomanufacturing technology [67, 71, 99107]. Based on all the advanced characteristics of 3D printing, 4D printing incorporates a time-dependent dynamic process in the fabrication design, which is believed to further revolutionize current tissue/organ fabricating platforms.…”
Section: Application Of 4d Printing In Tissue and Organ Regenerationmentioning
confidence: 99%
“…[49] SLA, [50] FDM, [51] inkjet printing, [52] and extrusion-based 3D printing techniques, [53] have been used for the fabrication of various biomedical components such as organs, prosthesis, dental, and bone implants. 3D printing of nanocomposites enables the achievement of the properties of living tissues such as electronic responsivity, conductivity, and chemical activity in customized fashion.…”
mentioning
confidence: 99%
“…[56] It is worth noting that nanomaterials can also be attached to the surface of an already 3D printed structure, in order to either add functionality or improve a desired performance such as increase bioactivity in biomedical and lab-on-a-chip devices. [57] Holmes et al [51] reported a chemical functionalization process for the attachment of bioactive hydroxyapatite nanoparticles (nHA) on the surface of an FDM-printed scaffold for bone growth. The nHA nanoparticles are active sites for full growth of cells, while the printed scaffold allows differentiation, bone formation, and vascular cell growth.…”
mentioning
confidence: 99%